Pelatihan Manajemen Usaha dan Keuangan Berbasis Digital Bagi Pelaku Usaha Pertanian di Desa Jabong - Istiqomah, Asti; Nuva; Hidayat, Nia Kurniawati; Amanda, Dea; Osmaleli (Jurnal ETAM, 2025)
Agriculture is an important sector for the survival of the community. The number of agricultural products is increasing, but in line with the competition for land use with non-agricultural ones. One alternative for agriculture with limited land use is hydroponics. One of the farmer groups that implements the hydroponic system and product processing is Jabong Hydro Farm in Jabong Village, Subang Regency. The training activities aim to increase the capacity of farmers and agricultural business actors in digital-based business and financial management. The training was held in the Jabong Hydro Farm area and was attended by 26 farmers and business actors. The results of the training showed that the Agricultural-Based MSME Product Standardization training encouraged 88% of farmer participants to take care of the Household Industry Food Production Certificate. The training on Calculating the Cost of Goods Sold (HPP) and Determining the Selling Price of Products showed that after participating in the training, 100% of participants knew what HPP was, the components of HPP and how to calculate HPP. Furthermore, Digital Marketing Training caused the greatest increase in understanding regarding various types of digital marketing. The digital-based Simple Bookkeeping Training for MSMEs stated that farmers will implement digital business financial recording with applications on mobile phones because it is considered very helpful and easy to do.